A cell culture-derived whole virus influenza A vaccine based on magnetic sulfated cellulose particles confers protection in mice against lethal influenza A virus infection. Issue 50 (7th December 2016) - Pieler, Michael M.; Frentzel, Sarah; Bruder, Dunja; Wolff, Michael W.; Reichl, Udo
Graphical abstract: Highlights: Vaccine purification and formulation with magnetic sulfated cellulose particles (MSCP). Influenza A virus MSCP vaccine for immunization of mice against lethal challenge. Purification and formulation of low-cost veterinary vaccines. Fast and simple purification for screening studies. Purification of viral vectors for gene therapy. Abstract: Downstream processing and formulation of viral vaccines employs a large number of different unit operations to achieve the desired product qualities. The complexity of individual process steps involved, the need for time consuming studies towards the optimization of virus yields, and very high requirements regarding potency and safety of vaccines results typically in long lead times for the establishment of new processes. To overcome such obstacles, to enable fast screening of potential vaccine candidates, and to explore options for production of low cost veterinary vaccines a new platform for whole virus particle purification and formulation based on magnetic particles has been established. Proof of concept was carried out with influenza A virus particles produced in suspension Madin Darby canine kidney (MDCK) cells. The clarified, inactivated, concentrated, and diafiltered virus particles were bound to magnetic sulfated cellulose particles (MSCP), and directly injected into mice for immunization including positive and negative controls. We show here, that in contrast to the mock-immunized group, vaccination of mice with antigen-loaded MSCP (aMSCP) resulted in high anti-influenza A antibody responses and full protection against a lethal challenge with replication competent influenza A virus. Antiviral protection correlated with a 400-fold reduced number of influenza nucleoprotein gene copies in the lungs of aMSCP immunized mice compared to mock-treated animals, indicating the efficient induction of antiviral immunity by this novel approach. Thus, our data proved the use of MSCP for purification and formulation of the influenza vaccine to be fast and efficient, and to confer protection of mice against influenza A virus infection. Furthermore, the method proposed has the potential for fast purification of virus particles directly from bioreactor harvests with a minimum number of process steps towards formulation of low-cost veterinary vaccines, and for screening studies requiring fast purification protocols.